Análise exergética da produção do biodiesel por mistura binária de sebo bovino e óleo de soja - Marina Marques da Silva (2017)
Energy demand is growing rapidly due to population growth and the level of industrialization and technological innovations. The search for new technologies and the improvement of existing ones is becoming increasingly important to meet the needs of the population more efficiently and with less use of natural resources. Parallel to the importance of energy for the world that is set up, there is concern for environmental preservation, which is structured both in energy efficiency and exergetic optimization efforts and in investments in research, development and application of renewable resources and cleaner technologies , Such as biodiesel. Therefore, in this work, the exergy analysis of soybean and bovine tallow biodiesel was carried out by investigating the biodiesel production process of soybean and bovine tallow; Quantification of mass and energy flows; Analysis of the raw material and by-products of each subsystem of the biodiesel production of soybean and bovine tallow; Irreversibilities or destroyed exergy of each subsystem; Comparing the exergetic efficiency of soybean crop production, soybean oil extraction, soybean oil refining, and soybean and bovine tallow biodiesel. The analysis was made considering from the soybean cultivation to the biodiesel production, dividing each production route into its main control volumes. For soybean cultivation and oil extraction, data from the scientific literature were used to calculate the exergic efficiency according to the second law of thermodynamics. Data on the production of bovine sebum were not found in the literature and, therefore, it was not possible to perform the Exergetic analysis of bovine tallow production. On the other hand, the subsystems of oil production and refining and industrial production of biodiesel were analyzed from data collected at a biodiesel plant located in the state of Minas Gerais. From the analysis, it is found that the greatest irreversibilities are generated in the processes where irreversible thermochemical reactions occur, especially the reaction of transesterification and the need to continue researching to reduce the consumption of the inputs used, heat and mechanical work. The subsystem that presented lower exergética efficiency was the one of soybean cultivation (22%); On the other hand, the most efficient sub-system was soybean refining (88%). Therefore, it is concluded that a more detailed study of the soybean crop is necessary in order to identify the points in which the efficiency can be increased in order to make the system of production of soybean biodiesel more efficient and with less irreversibilities in the process